2000
DOI: 10.1116/1.1305972
|View full text |Cite
|
Sign up to set email alerts
|

Epitaxial thin films of MgO on Si using metalorganic molecular beam epitaxy

Abstract: Epitaxial cubic MgO thin films have been deposited on single crystal Si(001) substrates by metalorganic molecular beam epitaxy. The Mg source was the solid precursor magnesium acetylacetonate and a rf excited oxygen plasma was the oxidant. The growth process involved initial formation of an epitaxial β-SiC interlayer followed by direct deposition of a MgO overlayer. The films were characterized by in situ reflection high energy electron diffraction, x-ray diffraction, conventional and high resolution transmiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
25
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 30 publications
0
25
0
Order By: Relevance
“…To reduce the interfacial strain and facilitate epitaxy, epitaxial MgO has been deposited on Si using buffer layers. Using MOMBE, Niu et al have deposited epitaxial MgO on Si(001) substrates with β-SiC buffer layers [4]. Sharma et al have deposited epitaxial MgO on Si(001) with TiN buffer layers by pulsed laser deposition (PLD) [5].…”
Section: Introductionmentioning
confidence: 99%
“…To reduce the interfacial strain and facilitate epitaxy, epitaxial MgO has been deposited on Si using buffer layers. Using MOMBE, Niu et al have deposited epitaxial MgO on Si(001) substrates with β-SiC buffer layers [4]. Sharma et al have deposited epitaxial MgO on Si(001) with TiN buffer layers by pulsed laser deposition (PLD) [5].…”
Section: Introductionmentioning
confidence: 99%
“…[5,6] Silicon homoepitaxy has been studied extensively, [7,8] with both numerical simulations of the reaction mechanism [9,10] and experimental studies having been carried out. [7,8] They deal, for example, with the adsorption of hydrogen during CVD and the resulting passivation, [11,12] or etching of the surface, [13,14] depending on the process parameters.…”
Section: Methodsmentioning
confidence: 99%
“…[5] The growth of epitaxial MgO films on semiconductor substrates such as Si and GaAs is an important research area with many technological applications. For the growth of MgOfilms on Si and/or GaAs, various growth techniques, such as pulsed laser deposition, [6±8] electron beam evaporation, [9,10] sputter deposition, [11] metal±organic (MO)-CVD, [12] and metal±organic molecular beam epitaxy, [13] have been employed. Although the lattice misfit of MgO with respect to silicon is ±22.5 %, the use of buffer layers has allowed high quality MgO epitaxial films to be grown on Si substrates.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests the possibility of a magnesium oxide ͑MgO͒ interface between the 6H-SiC substrate and the functional oxide film to alleviate lattice strain without interfering with any desired interaction between the functional films and the substrate. While there is limited literature of MgO film deposition by molecular beam epitaxy ͑MBE͒, Niu et al 5 reported using metal organic molecular beam epitaxy to epitaxially grow crystalline MgO ͑001͒ on silicon ͑001͒ with a 200 nm thick interlayer of crystalline 3C-SiC ͑001͒. Yadivalli et al 6 reported homoepitaxial growth of MgO ͑001͒ using MBE.…”
mentioning
confidence: 99%